School Management in Improving Student Character Education (Case Study at Annida Tahfizhul Qur'an Middle School) - Luhurbudi, Maryam Ratnaningsih; Sumedi, Sumedi (Arfannur: Journal of Islamic Education, 2025)
School management is the management of education in schools to achieve the goals that have been set. This Research aims to find out how school management improves student character education. This Research uses a qualitative approach with descriptive methods, where data collection techniques include interviews, observation, and documentation. The research subjects were the principal, teachers, and students at Tahfizhul Qur'an Annida Middle School. Data analysis is done by sorting the data obtained, then analyzing it and drawing conclusions. The results of this Research are: (1) school management planning in character education is expressed through the school's vision, mission, and learning in teaching materials and activities at school; (2). Implementation of character education in schools through Integration in learning and extracurricular activities, the habituation of good character by all school elements, providing good examples and role models, and creating an atmosphere of character in schools (3). Evaluation of character education in schools through student personality reports and joint assessments with teachers and parents.